A National Framework for Sustainable Urban Transport Systems : Proposals for Improving Urban Transportation in Russian Cities - World Bank (World Bank, Moscow, 2013)
In many Russian cities, these growing demands for mobility are not adequately met by the existing urban transport infrastructure and services. Most municipalities have had difficulties in planning and managing the development of their urban transport systems in a coherent manner, which is a precondition for successful resolution of the existing transport problems. In addition, there is a need to develop and put in place a sound legal and regulatory framework. Thus, in order to create favorable conditions for addressing the existing transport problems, there is a need to develop a national framework that would contribute to the creation of pre-requisites for sustainable development of urban transport systems. The purpose of this work is to develop proposals for the formation of the national framework for improvement of the quality and sustainability of urban transport and road traffic safety in Russian cities.